Theoretical study on the reaction mechanism of OH radical with Z(E)-CF3CHCHF. Issue 3 (2nd January 2019) - Xu, Chao; Wang, Chaoyang; Li, Bo; Hu, Linping; Gu, Feng Long
Abstract : The comprehensive transformation mechanism and kinetics of Z ( E )-CF3 CHCHF initiated by OH radicals were investigated by performing quantum chemical calculations. Abstract : Understanding the atmospheric fate of hydrofluoroolefins (HFOs) is of great significance to assess their potential risk to the environment. As an important type of HFO, the comprehensive transformation mechanism and kinetics of Z ( E )-CF3 CHCHF initiated by OH radicals were investigated by performing quantum chemical calculations at the CCSD(T)/aug-cc-pVTZ//MP2/cc-pVDZ level. The results show that the OH-addition pathways are the most favorable for the title reaction. The rate constants are obtained by transition state theory with Wigner tunneling correction (TST/W). The calculated total rate constants are in good agreement with the experimental data. At 298 K, the computed rate constant and lifetime of Z ( E )-CF3 CHCHF are 9.66 × 10 −13 (4.02 × 10 −13 ) cm 3 molecule −1 s −1 and 12.3 (29.7) days, respectively, which demonstrates that Z ( E )-CF3 CHCHF is atmospherically persistent.